Research in the Social Scientific Study of Religion, Volume 30 - Cheruvallil-Contractor, Sariya; W., Hood, Ralph (Research in the Social Scientific Study of Religion, 2020)
The 30th volume of Research in the Social Scientific Study of Religion consists of two special sections, as well as two separate empirical studies on attachment and daily spiritual practices. The first special section deals with the social scientific study of religion in Indonesia. Indonesia is a predominantly Muslim country whose history and contemporary involvement in the study of religion is explored from both sociological and psychological perspectives. The second special section is on the Pope Francis effect: the challenges of modernization in the Catholic church and the global impact of Pope Francis. While its focus is mainly on the Catholic religion, the internal dynamics and geopolitics explored apply more broadly.